Synthesis, spectroscopic characterization and molecular modeling of a tetranuclear platinum(II) complex with thiazolidine-4-carboxylic acid - Corbi, Pedro P.; Formiga, Andre L. B.; Bonk, Fabio A.; Quintao, Frederico A.; Ferraresi, Diego K. D.; Lustri, Wilton R.; Massabni, Antonio C. [UNESP] (Elsevier B.V., 2012)
The synthesis, spectroscopic characterization and molecular modeling of a novel tetranuclear platinum(II) complex with thiazolidine-4-carboxylic acid (THC) are described. Elemental analysis is consistent with the composition PtCl2C4H7NO2S-H2O. Infrared (IR) spectroscopic results and solid-state C-13 and N-15 nuclear magnetic resonance (NMR) data indicate coordination of the ligand to Pt(II) through the nitrogen and sulfur atoms. The square planar geometry of the platinum(II) complex is completed by chlorine atoms. Density functional theory (OFF) suggests the formation of a tetrameric cluster as the most probable structure, where each THC molecule bridges between two metal centers. The compound is insoluble in water. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Thiazolidine-4-carboxylic acid; Platinum(II) complex; Infrared spectroscopy; Solid-state NMR; Molecular modeling